2008
DOI: 10.4314/ejesm.v1i1.41571
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Methods Of Spear grass (<i>Imperata cylindrica</i> L.) Control in the Derived Savanna Zone Of Nigeria.

Abstract: Spear grass (Imperata cylindrica, L.) is one of the most serious weed problems facing farmers in the derived savanna zone of Nigeria. The study was designed to evaluate various control methods that would effectively control this noxious weed and increase crop yield in an environmentally sustainable way. The treatments were laid out in a randomized complete block design and these included: Glyphosate only applied at 1.8kg per hectare eight weeks after planting cassava; Glyphosate applied at 1.0kg per hectare ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The abundance of A. sessilis an emergent weed in site D is an indication of a swampy condition. The researchers reported that it is because of the varied habitat types and high levels of precipitation in parts of West Africa that there is a large diversity of aquatic plant species in the region [42]. Water logging plays an important role in determining plant distribution in terrestrial communities , since the consequences to plants may be fatal A. sessilis prefers places with constant or periodically high humidity but may however tolerate extremely dry conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of A. sessilis an emergent weed in site D is an indication of a swampy condition. The researchers reported that it is because of the varied habitat types and high levels of precipitation in parts of West Africa that there is a large diversity of aquatic plant species in the region [42]. Water logging plays an important role in determining plant distribution in terrestrial communities , since the consequences to plants may be fatal A. sessilis prefers places with constant or periodically high humidity but may however tolerate extremely dry conditions.…”
Section: Discussionmentioning
confidence: 99%